Feyerabend: The Most Valuable Philosopher of the Twentieth Century - Munévar, Gonzalo (Filozoficzne Aspekty Genezy, 2024)
This chapter will argue that Paul K. Feyerabend is the most valuable philosopher of the twentieth century. Given the extraordinary importance of science in the twentieth century, the most valuable philosopher of the century should be someone who has given us the most significant understanding of the nature of science and its impact on the rest of the human experience — Feyerabend did precisely that. I will contrast his accomplishments with those of other important philosophers such as Kuhn, Popper, Wittgenstein, Heidegger, Rawls, Carnap, Quine, Russell, and Dewey. Of critical importance in this regard will be Feyerabend’s case for theoretical pluralism, which overturned key ideas from analytical philosophy by demonstrating that all scientific rules, no matter how sound and empirically fruitful, must allow for exceptions. Science as we know it could not have progressed without scientists breaking well-established methodological norms. He argues, with Galileo, that observation assumes theory. As Feyerabend tells us, “We need a dream-world in order to discover the features of the real world we think we inhabit (and which may actually be just another dream-world)”.